Airport Outings: The Coalitional Possibilities of Affective Rupture. Issue 4 (1st October 2016) - Spalding, Sally J.
ABSTRACT: This article advances a theory of affective rupture and explores its potential as grounds for coalition across substantial lines of difference. Using the unanticipated "outing" of gender-normative breast cancer patients at airport security checkpoints as a case study, I argue that it is in moments of unanticipated scrutiny and vulnerability that existing affective economies are disrupted and new affiliations are facilitated among groups with asymmetrical privilege and contesting agendas. In the case of breast cancer patients, I argue that this affective rupture at the security checkpoint can be grounds for coalition with transwomen who have been similarly mistreated by the Transportation Security Administration for their gender variance. I conclude with a brief sketch of the possibilities and limitations of such a coalition.